2000
DOI: 10.1006/viro.2000.0627
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Dependent Induction of Type I Interferons by Poliovirus in Human Mononuclear Blood Cells Requires the Type II Fcγ Receptor (CD32)

Abstract: The induction of type I interferons (IFNs) in peripheral blood mononuclear cells (PBMCs) can be triggered by viral infection or exposure to viral glycoproteins. Here we show that the IFN-alpha-inducing capacity of attenuated poliovirus vaccine strains is dramatically enhanced in the presence of human polyvalent immunoglobulin G (IgG). The transcription of both IFN-alpha and IFN-beta genes was detected by RT-PCR in stimulated cells. This antibody-dependent activation of type I IFNs genes was also observed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 35 publications
5
47
1
Order By: Relevance
“…Stimulatory concentrations of PG, for example, were only reached with proliferating bacteria. A similar observation was made by several groups working on viral pDC activation via nucleic acids that seemed to be dependent on viral replication (26,57,70). Therefore, ongoing bacterial DNA and RNA synthesis may represent a prerequisite for passing the threshold concentration of nucleic acids necessary for TLR stimulation.…”
Section: Discussionsupporting
confidence: 69%
“…Stimulatory concentrations of PG, for example, were only reached with proliferating bacteria. A similar observation was made by several groups working on viral pDC activation via nucleic acids that seemed to be dependent on viral replication (26,57,70). Therefore, ongoing bacterial DNA and RNA synthesis may represent a prerequisite for passing the threshold concentration of nucleic acids necessary for TLR stimulation.…”
Section: Discussionsupporting
confidence: 69%
“…This contrasts with other viruses, such as HIV and poliovirus, with which antibody complexing had a positive effect on the induction of IFN-a production by PBMC [25,26].…”
Section: Discussioncontrasting
confidence: 58%
“…This cellular duo can be further stimulated with immune complexes (Ab-RNA/DNA, Abviruses), and therefore represents a crucial player in the initiation and amplification of antimicrobial responses as well as the propagation of autoimmune diseases such as systemic lupus erythematosus. [9][10][11] More detailed studies on human B-cell populations have shown that peripheral blood-derived naive and memory B cells express distinct levels of TLR6, 7, and 9. Indeed, TLR6, 7, 9, and 10 are barely expressed by circulating naive B cells, 7 whereas memory B cells display a higher sensitivity to TLR activation with a concomitant higher capacity for differentiation into plasma cells.…”
Section: Tlr Expression In Normal and Neoplastic B Cells Normal B-celmentioning
confidence: 99%